The effect of work stress on the performance of employees psychological well-being and subjective well-being (Study at PT. Global Insight Utama Bali area) - Tsalasah, Ekromi Fraida; Noermijati, Noermijati; Ratnawati, Kusuma (MEC-J (Management and Economics Journal), 2019)
This study aimed to analyze the effect of work stress on employee performance, analyze the effect of work stress on psychologicall well-being, to analyze the influence of psychologicall well-being of the employee's performance, analyze the effect of work stress on subjective well-being, to analyze the influence of subjective well-being of the performance employee, psychologicall To analyze the effect of well-being as mediation work stress on employee performance, and analyze the influence of subjective well-being as mediation work stress on employee performance. Mechanical analysis using PLS. The analysis showed that the effect of work stress on employee performance, job stress affect the well-being psychologicall, psychologicall well-being affect the performance of the employee